Impact of Formative Assessment with Immediate Feedback on Academic Performance in Undergraduate Medical Students - Muhammad Nadeem Shafique, Qaiser Javed, Muhammad Yawar Khan Javeria Sarfraz, Attia Sheikh, Asma Siddiqui, Farah Naz Tahir, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Formative assessment with immediate feedback has emerged as a vital pedagogical tool to enhancelearning outcomes in medical education. This experimental study aimed to evaluate the impact offormative assessments accompanied